Comparative evaluation of shear bond strengths of veneering porcelain to base metal alloy and zirconia substructures before and after aging – An in vitro study - Sreekala, Laju (J Int Soc Prev Community Dent, 2015)
OBJECTIVE: The aim of this study was to evaluate and compare the shear bond strength of veneering porcelain to base metal alloy and zirconia substructures before and after aging. Scanning electron microscopy (SEM) was used to determine the failure pattern. MATERIALS AND METHODS: Twenty rectangular blocks (9 mm length × 4 mm height × 4 mm width) of base metal alloy (Bellabond plus, Bego, Germany) and zirconia (Will ceramZ zirconia K block) were fabricated for shear bond strength test. Surface of the base metal alloy block (4 mm × 4 mm area) was veneered with corresponding veneering porcelain (Ivoclar, IPS classic, vivadent). Similarly, surface of the zirconia rectangular block (4 mm × 4 mm) was veneered with corresponding veneering ceramic (Cercon ceram kiss, Degudent). Out of forty rectangular porcelain veneered core specimen, ten porcelain veneered base metal alloy specimen and ten porcelain veneered zirconia specimen were immersed in water at 37°C for one month to simulate the oral environment. RESULTS: On comparison, the highest shear bond strength value was obtained in porcelain veneered base metal alloy before aging group followed by porcelain veneered base metal alloy after aging group, Porcelain veneered zirconia before aging group, porcelain veneered zirconia after aging group. SEM analysis revealed predominantly cohesive failure of veneering ceramic in all groups. CONCLUSION: Porcelain veneered base metal alloy samples showed highest shear bond strength than porcelain veneered zirconia samples. Study concluded that aging had an influence on shear bond strength. Shear bond strength was found to be decreasing after aging. SEM analysis revealed cohesive failure of veneering ceramic in all groups suggestive of higher bond strength of the interface than cohesive strength of ceramic. Hence, it was concluded that veneering ceramic was the weakest link.